The importance of familial risk factors in children with ADHD: direct and indirect effects of family adversity, parental psychopathology and parenting practices on externalizing symptoms - Jendreizik, Lea Teresa; Hautmann, Christopher Jan; Wirth, Elena von; Dose, Christina; Thöne, Ann-Kathrin; Treier, Anne-Katrin; Banaschewski, Tobias; Becker, Katja; Brandeis, Daniel; Geissler, Julia; Hebebrand, Johannes; Hohmann, Sarah; et al. (Child and adolescent psychiatry and mental health, 2022)
Children experiencing unfavorable family circumstances have an increased risk of developing externalizing symptoms. The present study examines the direct, indirect and total effects of family adversity, parental psychopathology, and positive and negative parenting practices on symptoms of attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) in children with ADHD.